French Language Learning Media Based on Project-Based Learning Assisted by the Pear Deck Application - Zudya Pratidina; Mukhtar Mukhtar; Naeklan Simbolon (RIRAI Publisher, 2024)
The purpose of this research is to determine (1) the feasibility of learning media assisted by the Pear Deck application based on project-based learning (PjBL). (2) determine the effectiveness of PjBL-based learning media. The research method is R&D using the Borg and Gall development models. This research was conducted in class XI SMAN 1 Lubuk Pakam, totaling 28 students. The research subjects are material experts, media experts, and design experts. The research results show that: (1) the learning material expert test criteria are very good (94%); (2) the learning media expert test criteria are very good (93%); and (3) the learning design expert test criteria are very good (94%). The results of submitting a hypothesis can prove that: (1) learning media assisted by the PjBL-based Pear Deck application is suitable for use (2) The learning media assisted by the PjBL-based Pear Deck application is effective to use. The average effectiveness of students' French learning outcomes in using the PjBL-based Pear Deck Application in the experiment class was 86.42%, and the average effectiveness of the average effectiveness of students who used picture and book learning media in the control class was 49.5%. The posttest results obtained a value of Tcount = 7.08 at a significant level of α = 0.05, with dk 27 obtaining Ttable = 1.674, so that Tcount > Ttable, namely 7.08 > 1.674. The use of learning media assisted by the PjBL-based Pear Deck application is very feasible and effective.